Нежное дыхание смерти: роман / Анна Малышева - Малышева Анна Витальевна (Детектив, 2004)
Экземпляры: ф.22 (20171113) / Инвентарный номер: 57838 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: М 20 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44